Initial Reading Difficulties in Second-Grade Elementary School Students - Nur Chumairoh; Sukardi (Universitas Pendidikan Ganesha, 2023)
Beginning reading is an ability that students must master in elementary school. In the implementation process, students who still have difficulty in beginning reading are sometimes found. These difficulties become an obstacle in the student's learning process because success in mastering reading skills at the initial reading stage will impact the development of subsequent reading skills. This research aims to analyze the types of initial reading difficulties in students, the factors that influence initial reading difficulties in students, and the efforts made by teachers to overcome initial reading difficulties in second-grade elementary school students. This research uses descriptive qualitative methods. Data collection techniques are done through interviews, observation, tests, and documentation. The study results showed that three second-grade students had difficulty reading initially. In research, it is known that the types of initial reading difficulties in students are: (a) not fluent in reading, (b) many errors in reading, (c) difficulty distinguishing similar letters, (d) inability to understand symbols sounds. Factors that influence students' initial reading difficulties are physiological, intellectual, environmental, and psychological factors. Efforts made by teachers to overcome students' initial reading difficulties are: (a) giving assignments to students, (b) providing additional hours after school, (c) preparing reading learning media such as alphabet letter posters, letter cards, and books that support students' initial reading ability, (d) teaching using the alphabet method.